Keanekaragaman Bivalvia di Pesisir Wisata Pantai Depok, Pekalongan: Bivalvia, Depok Beach Pekalongan Regency, Diversity, Dominance, Evenness. - Nafilah, Daffa Ulwan; Wijayanti, Erna (Jurnal Pendidikan Biologi Undiksha, 2023)
Pekalongan is an area that has a fairly long coastline because it is located on the northern coastline of Central Java. However, there is still not much research related to beach conditions in Pekalongan. One of the Depok beach tours in Pekalongan Regency has also not been explored much, especially regarding the study of the diversity of marine life in the area. Marine biota that are often found in coastal areas are clams (Bivalvia). Therefore this study aims to measure the diversity of bivalves in the coastal tourism area of Depok, Pekalongan Regency. The method used is the quadrant method by adopting a sampling transect schematic. Data analysis used the Shanon-Weiber diversity index, evenness index, and dominance index. The results of the study found that there were 13 species consisting of 7 genera, 6 families, and 5 orders with a total of 224 individuals of Bivalvia. Diversity index value -2.126.. Evenness index value -0.829. The dominance index value is 0.153. The low index values for diversity, evenness, and dominance are influenced by environmental factors and human activity factors.